Enhancing RNAi Efficiency to Decipher the Functional Response of Potential Genes in Bemisia tabaci AsiaII-1 (Gennadius) Through dsRNA Feeding Assays - Kaur, Ramandeep; Gupta, Mridula; Singh, Satnam; Joshi, Neelam; Sharma, Abhishek (Frontiers in Physiology, 2020)
Whitefly Bemisia tabaci is a global invasive pest that causes substantial losses to agricultural crops worldwide either by direct feeding or vectoring numerous plant viruses. Management with insecticides remains a big challenge due to its rapid resistance development potential as well as the impact of these chemicals on non-target organisms. Thus, in search of alternate and novel pest management strategies RNA interference (RNAi) has come up as potential future tool in this direction. The present study targets nine potential genes (Aquaporin (AQP), Calcitonin (CAL), CyclophilinB (CYCP), Knottin-1 (k-1), Heat shock proteins (Hsp20, Hsp40 and Hsp70), SWItch/Sucrose Non-fermentable (SNF7) and inhibitor of apoptosis (IAP) of whitefly that have been implicated to play a role in various vital physiological functions and virus transmission. The RNAi mediated knockdown efficiency of these genes has been improved through the conjugation of respective target gene dsRNA with CQD (carbon quantum dots) nanoparticles or simultaneous knockdown of dsRNA specific gut nucleases. The studies revealed that feeding of dsRNA (40 μg/ml sucrose diet) of the target gene(s) either conjugated with CQD or along with dsRNA against dsRNase (dsdsRNase) (40 μg/ml sucrose diet) enhanced the RNAi efficiency by 24–89% compared to whiteflies fed with naked dsRNA of the same target gene. The studies provide insights about the functional role of various genes in whitefly, which can possibly be exploited for the management of this pest in the future.